Social assimilation and labor market outcomes of migrants in China - Shu Cai; Klaus F. Zimmermann (University of Bonn, Center for Development Research (ZEF), 2020)
Previous research has found identity to be relevant for international migration, but has neglected internal mobility as in the case of the Great Chinese Migration. However, the context of the identities of migrants and their adaption in the migration process is likely to be quite different. The gap is closed by examining social assimilation and the effect on the labor market outcomes of migrants in China, the country with the largest record of internal mobility. Using instrumental variable estimation, the study finds that identifying as local residents significantly increases migrants' hourly wages and reduces hours worked, although their monthly earnings remained barely changed. Further findings suggest that migrants with strong local identity are more likely to use local networks in job search, and to obtain jobs with higher average wages and lower average hours worked per day.
Keywords: J22; J31; J61; Z13; 330; Social assimilation; identity; labor market; migration